Dynamics of labile soil organic carbon during the development of mangrove and salt marsh ecosystems - Cui, Lina; Sun, Huimin; Du, Xuhua; Feng, Wenting; Wang, Yugang; Zhang, Jinchi; Jiang, Jiang (Ecological indicators, 2021)
•Soil organic carbon (SOC) increased over time in mangrove forest, while not in S. alterniflora sites.•Labile organic carbon (LOC) increased over time in Spartina alterniflora sites.•The proportion of resistant SOC increased over time in mangroves, contributed to SOC stabilization. Labile fractions of soil carbon pools are sensitive to environmental changes, which would influence the stabilization of soil carbon. However, it is unclear whether the dynamics of labile organic carbon (LOC) and soil organic carbon (SOC) are coupled and how they influence each other in coastal wetland. The present work investigated the trends of soil carbon fractions among mangrove and Spartina alterniflora communities with different stand ages (1, 5, 10, and 15 years), at Quanzhou Bay Estuary Wetland Nature Reserve, China. We found that SOC in a mangrove ecosystem increased over time, while there was no significant trend in S. alterniflora dominated ecosystems. The highest LOC of mangrove appeared in 5-year-old communities, and then decreased with stand age. In S. alterniflora communities, content of labile fractions increased with the stand age. These trends indicated different soil carbon dynamics when comparing mangrove and S. alterniflora ecosystems. The development of mangroves promoted accumulation of recalcitrant carbon, while S. alterniflora ecosystems contributed to an increase of labile carbon. This phenomenon is probably caused by the characteristics of vegetation and the hydrological conditions. Mangroves contribute more refractory organic carbon to the soil carbon pool, while accumulation of LOC in S. alterniflora communities may inhibit the stabilization of SOC. Our study on the relationship of LOC and SOC implies that complex interactions occur among soil carbon pools and environmental conditions in coastal wetlands, suggesting soil carbon models should take into account decoupled dynamics of LOC and SOC.